The Lower Cretaceous Centenario Formation: A subsurface unit in the northeastern border of the Neuquén Basin revisited. (June 2019) - Iñigo, J.F.P.; Pazos, P.J.; Novara, M.E.; Comerio, M.
Abstract: The Centenario Formation in the NE region of the Neuquén Basin is a lithostratigraphic unit that has been historically ascribed to continental deposits, being time-equivalent of the Agrio Formation in the basin border. The study of both the Lower and the Upper Members of the unit through detailed core analysis, electrofacies well correlation and seismic interpretation, was used to define depositional trends, main stratigraphic surfaces and develop paleoenvironmental models in the basin margin. The Centenario Formation presents at least two transgressive-regressive intervals. This mixed sandstone-shale succession is marine to marginal marine in the lower member and marine, marginal marine and fluvial in the upper member. The overall environmental configuration and evolution allow defining sedimentary supply from the NE and E. Facies characterization, paleoenvironmental interpretation, in addition to its vertical evolution and geographic distribution constitute key elements to evaluate and define remaining hydrocarbon potential for this interval, as well as allowing integration between outcrop and subsurface data. Highlights: The Centenario Fm. in the NE border of Argentinean Neuquen Basin shows a different paleoenvironment from that of the rest of the basin. Centenario Fm. is interpreted as a marginal marine system with fluvial deposits, and organized in transgressive-regressive cycles. Sedimentary infill is the result of supply from the eastern border of the basin and the reworking of previous eolian deposits. Excellent textural parameters explain the unusual hydrocarbon accumulations in the Centenario Fm. at the Rio Colorado Productive Trend.